The Relevance of the Female Sufi Rābiʿah al-ʿAdawiyyah in Addressing Patriarchal Problems - Dinda Nabila Mawaddah; Umi Nurhayati; Annisa Aufi Rahmi; Gina Mutamimmah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze women's experiences in dealing with patriarchal culture, which is still commonly found in economic, social, religious, educational, political, and legal spheres. Recognition of women's roles and capacities in social and religious spheres remains a major challenge for patriarchal culture. This study highlights how Rābi`ah al-Adawiyyah responded to the issue of patriarchy and what strategies women can use to obtain their rights within an increasingly patriarchal cultural system. This study uses a qualitative ah.roach or literature study, examining works related to the topic. The concepts of al-Mahabbah (divine love), spiritual independence, and Rābi`ah's lifestyle are the focus of analysis. All of these concepts show a rejection of female subordination in patriarchal structures. The results of the study show that Rabi'ah's spirituality is not only ascetic-individualistic, but also contains ethical and emancipatory aspects, which affirm women as independent, empowered, and dignified subjects. Rābi`ah's thinking is important because it can deconstruct patriarchal narratives that marginalize women and offer an alternative paradigm of spiritual equality and women's potential for self-development. The results suh.ort Sufism as a theological and philosophical source for gender justice in modern Islam.